Fiscal and Monetary Policies in Tackling Inflation Amid Rising Global Energy Prices - Komarudin; Sugiartini, Pegi (Asosiasi Persatuan Pengusaha Muda Teknik Informatika, 2025)
Inflation is a major challenge faced by many countries, especially amid rising global energy prices. This increase has the potential to disrupt people's purchasing power and economic stability. This study aims to explore the effectiveness of fiscal and monetary policies in dealing with inflation triggered by fluctuations in energy prices. The study used a mixed approach with quantitative analysis through multiple linear regression on secondary data from three countries (Indonesia, Brazil, Germany) and in-depth interviews with 12 economists to obtain a qualitative perspective. The results of the analysis show that energy prices have a significant impact on inflation (b3 = 0.75, p < 0.001), and fiscal policies, such as subsidies, can ease the burden of inflation. Coordination between fiscal and monetary policies has proven crucial to achieve economic stability. It was found that 75% of respondents agreed that policy integration can increase effectiveness in tackling inflation. The study concludes that a synergistic approach between fiscal and monetary policy is urgently needed to confront complex inflation challenges amid energy market uncertainty. This research contributes by providing a comprehensive framework for integrating fiscal and monetary policies to effectively manage inflation driven by rising global energy prices.